LEGAL ACTIVITY AS A TYPE OF LEGAL WORK - Vadym O. Anokhin (Alfred Nobel University Journal of Law)
The article is devoted to the study of the legal activities of the legal support units of state bodies, in particular the bodies of the state tax service, taking into account a certain retrospect. The article contains references and citations of scientists whose research subjects were legal work, the activities of the legal service and legal support in the state tax service bodies. The article stated that in the organization of the activities of any enterprise or organization there are always functional divisions that ensure the performance of statutory tasks and functions, and those that provide, which, in particular, include legal. As a result of the analysis of the relations between the administration of the enterprise and the institution of the organization, the article proposes models of such interaction with various entities that provide legal assistance. Among the correlation of such categories as "legal work" and "legal activity", the research found its place and generalization of the principles of legal activity. Scientists research allows us to claim that the specificity of a lawyer's activity contains law enforcement activity of employees of other services and depends on the body`s level whose legal side of activity they provide. As a result of the analysis of the work of lawyers and scientists, it was concluded that legal work is an organizational process that ensures the correct and effective implementation of current legislation at every stage of both economic activity and state administration. The proposed work contains different definitions and understandings of the term "legal activity", that indicates the multiplicity of approaches to the definition of the considered category. The work proposes a structure of legal activity, which is formed by subjects, objects, legally significant actions and events. The analysis of practical activities in the bodies of the state tax service allows us to conclude that activities with the application of legal norms concern not only legal divisions, but all structural ones, including functional ones.